Risk factors for self-harm in people with epilepsy - Owen Pickrell (Journal of Neurology, 2018)
Objective:To estimate the risk of self-harm in people with epilepsy and identify factors which influence this risk.Methods: We identified people with incident epilepsy in the Clinical Practice Research Datalink (CPRD), linked to hospitalization and mortality data, in England (01/01/1998-03/31/2014). In Phase 1, we estimated risk of self-harm among people with epilepsy, versus those without, in a matched cohort study using a stratified-Cox proportional hazards model. In Phase 2, we delineated a nested case-control study from the incident epilepsy cohort. People who had self-harmed (cases) were matched with up to 20 controls. From conditional logistic regression models, we estimated relative risk of self-harm associated with mental and physical illness comorbidity, contact with healthcare services and antiepileptic drug (AED) use.Results: Phase 1 included 11,690 people with epilepsy and 215,569 individuals without. We observed an adjusted hazard ratio of 5.31 (95% CI 4.08-6.89) for self-harm in the first year following epilepsy diagnosis and 3.31 (95% CI 2.85-3.84) in subsequent years. In Phase 2, there were 273 cases and 3,790 controls. Elevated self-harm risk was associated with mental illness (OR 4.08, 95% CI 3.06-5.42), multiple General Practitioner consultations, treatment with two AEDs versus monotherapy (OR 1.84, 95% CI 1.33-2.55) and AED treatment augmentation (OR 2.12, 95% CI 1.38-3.26). Conclusion: People with epilepsy have elevated self-harm risk, especially in the first year following diagnosis. Clinicians should adequately monitor these individuals and be especially vigilant to self-harm risk in people with epilepsy and comorbid mental illness, frequent healthcare service contact, those taking multiple AEDs and during treatment augmentation.